Breast Implant-Associated Anaplastic Large Cell Lymphoma. (28th May 2020) - Moori, P. L.; Ibison, F.; Jacob, D.; Iddon, J.
Abstract : Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a rare, non-Hodgkin lymphoma which arises within the capsules of breast implants. These particular tumours have expression of CD30 and are negative for Anaplastic Lymphoma Kinase (ALK). Here, we report a case of BIA-ALCL in a 48-year-old woman post breast reconstruction. This case report is aimed at raising awareness and education on the significance of considering the development of BIA-ALCL in cases where cytology is negative and helping better understand this disease process.